Foreign direct investment in Vietnam - The case of American firms - Phung, Xuan Nha (ĐHQGHN, 2017)
In recent years American firms have rapidly increased their presence among foreign firms in Vietnam. By 1999, American investment was among the top ten largest in Vietnam. By the end of 2003, there were about 400 American firms in Vietnam with a total registered capital amounting to US$1308 million, accounting for 3.54% of the total registered FDI in Vietnam (MPI report, September 2003). However, compared with other foreign investors in Vietnam, American investors do not appear to be very successful and they went out of the top ten largest in Vietnam by the end of 2003.